2019
DOI: 10.3390/ani9050265
|View full text |Cite
|
Sign up to set email alerts
|

Horses’ (Equus Caballus) Laterality, Stress Hormones, and Task Related Behavior in Innovative Problem-Solving

Abstract: Domesticated horses are constantly confronted with novel tasks. A recent study on anecdotal data indicates that some are innovative in dealing with such tasks. However, innovative behavior in horses has not previously been investigated under experimental conditions. In this study, we investigated whether 16 horses found an innovative solution when confronted with a novel feeder. Moreover, we investigated whether innovative behavior in horses may be affected by individual aspects such as: age, sex, size, motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 88 publications
(140 reference statements)
1
17
0
Order By: Relevance
“…Male grackles (Quiscalus lugubris) that were less afraid of novelty, more exploratory, and more persistent were more likely to succeed in opening a box containing food (Overington et al, 2011), and the main predictor of success for wild hyenas in obtaining food from a puzzle box was diversity of techniques tried, with the primary inhibitor being neophobia (Benson-Amram and Holekamp, 2012). Neophobia also seems to explain speed of problem-solving in raccoons (Procyon lotor): less neophobic and more persistent individuals were more likely to solve a puzzle-box task (Daniels et al, 2019), and horses (Equus caballus) that were more active, more tenacious, and better at inhibition control were better able to feed from a novel feeder (Esch et al, 2019). Amici et al's (2019) meta-analysis of 38 studies of foraging tasks in 20 species of birds and mammals showed that individuals that are more explorative, neophilic and (to a lesser, non-significant extent) persistent are more prone to innovate; exploration more strongly predicted innovation in captive rather than wild animals.…”
Section: Social Network Positionmentioning
confidence: 99%
“…Male grackles (Quiscalus lugubris) that were less afraid of novelty, more exploratory, and more persistent were more likely to succeed in opening a box containing food (Overington et al, 2011), and the main predictor of success for wild hyenas in obtaining food from a puzzle box was diversity of techniques tried, with the primary inhibitor being neophobia (Benson-Amram and Holekamp, 2012). Neophobia also seems to explain speed of problem-solving in raccoons (Procyon lotor): less neophobic and more persistent individuals were more likely to solve a puzzle-box task (Daniels et al, 2019), and horses (Equus caballus) that were more active, more tenacious, and better at inhibition control were better able to feed from a novel feeder (Esch et al, 2019). Amici et al's (2019) meta-analysis of 38 studies of foraging tasks in 20 species of birds and mammals showed that individuals that are more explorative, neophilic and (to a lesser, non-significant extent) persistent are more prone to innovate; exploration more strongly predicted innovation in captive rather than wild animals.…”
Section: Social Network Positionmentioning
confidence: 99%
“…Similarly, individuals that are less stressed or anxious are better problem solvers due to increased persistence (e.g. house sparrows, Passer domesticus , Bókony et al, 2014; dogs, Canis familiaris , Bray et al, 2017; horses, Equus caballus , Esch et al, 2019). However, less exploratory individuals could be better problem solvers than exploratory ones, as exploratory individuals may dominate easily accessible resources (Huntingford et al, 2012), forcing less exploratory individuals to solve problems to access alternative resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that horses which opened feed storage rooms were older and had more access to pasture supports the role of opportunity in learning novel techniques. Nevertheless, individual personality [51,52] , especially the horses’ activity and emotionality [63] , may also account for differences in manipulative skills.…”
Section: Discussionmentioning
confidence: 99%